ANALISIS SPILLOVER EFFECT PENANAMAN MODAL ASING TERHADAP OUTPUT PERUSAHAAN DOMESTIK INDONESIA 2007-2013 - Samuel Kharis Harianto; Suyanto Suyanto; Sugeng Hariadi (CALYPTRA, 2018)
This study aims to analyze Foreign Investment which gives spillover impact on productivity growth of Indonesian manufacturing industry companies in 2007-2013.This study applies the application of quantitative analysis, using the data of the Annual Survey of Large and Medium Enterprises of the Central Statistics Agency of Indonesia (BPS). The data was processed by applying the method of panel data analysis and OLS regression. This research shows that PMA holistically gives a positive impact and gives different impacts to manufacturing industry sub-sector. With different findings, in each sector, different regulations related to PMA in Indonesian manufacturing industry are needed.